Hubungan Latihan Fisik dengan Depresi Postpartum - Jannah, Muliatul; Kusumaningsih, Meilia Rahmawati (Poltekkes Kemenkes Tanjung Karang, 2022)
Postpartum depression develops within a month of giving birth and can last up to a year. Depressive disorders that can occur can affect the health of the mother and newborn. Regular physical exercise during pregnancy and postpartum can have a comfortable effect on the body thereby reducing the risk of depression in pregnant women and after giving birth to children. The purpose of this study was to determine the relationship between physical exercise during the puerperium and postpartum depression. Research design Quasi Experiment approach to Non-Equivalent Control Group. The subjects of this study were 61 postpartum mothers at the Bangetayu Health Center Semarang which was carried out from July-December 2021. The study was conducted by examining the psychology (level of depression) in postpartum mothers before (pre-test) and after (post-test) physical exercise. The sampling technique was quota sampling with the research instrument using the Edinburgh Postnatal Depression Scale (EPDS) questionnaire with the Chi-Square test. There is a relationship between physical exercise (p-value=0.018) and postpartum depression (p-value=0.005) in the work area of Bangetayu Public Health Center Semarang. It is hoped that the results of this study can be used as information material regarding the relationship between physical exercise and postpartum depression. Postpartum mothers are expected to realize how important it is to keep the psyche from depression that can hinder physical exercise. For further researchers, it is hoped that they need to consider adding these variables with a larger number of respondents.